Insulin-Containing Wound Dressing Promotes Diabetic Wound Healing Through Stabilizing HIF-1α - Yang, Peilang; Wang, Di; Shi, Yan; Li, Mingzhong; Gao, Min; Yu, Tianyi; Liu, Dan; Zhang, Jie; Wang, Jizhuang; Zhang, Xiong; Liu, Yan (Frontiers in Bioengineering and Biotechnology, 2020)
HIF-1α is seen as a major regulator during wound healing and controls many wound healing processes, such as angiogenesis, extracellular deposition and re-epithelialization. Diabetic state plays a vicious effect on wound healing, and the destabilization of HIF-1α is a nonnegligible factor. An insulin loaded silk fibroin microparticles was prepared to release insulin by covering the wounds, and this material was proven to promote wound healing both in vitro and vivo studies. In this work, we found that this insulin containing wound dressing could accelerate diabetic wound healing by promote re-epithelialization, angiogenesis and extracellular matrix especially collagen deposition. Meanwhile, HIF-1α was stable and accumulate in insulin contained dressing group wound cells which was significantly unstable in the control group. In the further studies, we showed that MGO, the main kind of AGEs, accumulated significantly and causing the destabilization of HIF-1α in diabetic state. Insulin could alleviate MGO induced HIF-1α unstable state and promote HIF-1α target genes expression and its down-stream biological effect such as angiogenesis and wound extracellular matrix deposition.